Insecticide Residues on Poultry Manures: Field Efficacy Test on Selected Insecticides in Managing Musca Domestica Population - Song-Quan Ong,; Abdul Hafiz Ab Majid,; Hamdan Ahmad, (Tropical Life Sciences Research, 2017)
In this study, bifenthrin (Maxxthor SC, Ensystex Australasia Pty Ltd), imidacloprid (Prothor SC, Ensystex Australasia Pty Ltd) and fipronil (Regent®50SC, Bayer) were applied on the natural infest manures according to the manufacturer rate during a broiler breeding cycle. Solvent directimmersion extraction (SDIE) was used in detecting the target compound and later, quantification of the insecticide residues in field condition was investigated. The samples were prior cleaned up by solid-phase extraction (SPE) and analyzed by Ultra-Performance Liquid Chromatography (UPLC) - photodiode array (PDA) system. In the field trial, three insecticides were showed accumulation during the broiler breeding period and it is suggested that they acted as adulticides when applied on the poultry manures, this is supported by the significant correlation between the increment of insecticide residues to the reduction percentage of adult flies (<0.05). Fipronil showed significantly greater reduction on the adult fly compared to the other insecticides, in which the reduction rate compared to control population at the end of the broiler breeding period; fipronil, imidaclopril and bifenthrin reduced 51.51%, 28.30% and 30.84% of adult flies, respectively. Dalam kajian ini, bifenthrin (Maxxthor SC, Ensystex Australasia Pty Ltd), imidacloprid (Prothor SC, Ensystex Australasia Pty Ltd) dan fipronil (Regent®50SC, Bayer) telah digunakan pada najis ayam yang dikerumuni oleh lalat Musca domestica secara semulajadi dalam satu penternakan ayam daging kitaran. Pengekstrakan rendaman pelarut (SDIE) telah digunakan dalam mengesan kompaun racun dan kemudian, kuantifikasi dan kualifikasi racun serangga pada keadaan bidang telah disiasat. Sampel telah dibersihkan dengan pengekstrakan fasa pepejal (SPE) dan dianalisis oleh Ultra-Performance Liquid Chromatography (UPLC) - sistem fotodiod pelbagai (PDA). Dalam kajian lapangan ayam, tiga racun serangga telah menunjukkan pengumpulan dalam tempoh penternakan ayam dan ia dicadangkan bahawa tiga racun serranga bertindak sebagai racun lalat dewasa walaupun digunakan pada najis ayam, ini telah disokongi dengan korelasi yang signifikan antara kenaikan sisa-sisa racun serangga kepada peratusan pengurangan daripada lalat dewasa (<0.05). Fipronil menunjukkan pengurangan lalat yang lebih tinggi berbanding dengan racun serangga yang lain, di mana kadar pengurangan berbanding untuk mengawal lalat pada akhir tempoh pembiakan ayam daging; fipronil, imidaclopril dan bifenthrin mengurangkan 51,51%, 28,30% dan 30,84% lalat dewasa, masing-masing.